Clinical Characteristics for the Improvement of Cushing's Syndrome Complicated With Cardiomyopathy After Treatment With a Literature Review - Miao, Sisi; Lu, Lin; Li, Ling; Wang, Yining; Lu, Zhaolin; Zhu, Huijuan; Wang, Linjie; Duan, Lian; Xing, Xiaoping; Yao, Yong; Feng, Ming; Wang, Renzhi (Frontiers in Cardiovascular Medicine, 2021)
Background: Endogenous Cushing's syndrome (CS), also called hypercortisolism, leads to a significant increase in mortality due to excessive cortisol production, which is mainly due to cardiovascular disease. CS complicated with cardiomyopathies, which is a rare and severe condition, has rarely been reported in the literature. Objective: To investigate the clinical characteristics of CS complicated with cardiomyopathies, we retrospectively reviewed the clinical manifestations, laboratory results, cardiac imaging results and prognosis to further understand the diagnosis, treatment, and management of these cases. Methods: The clinical data of patients diagnosed with CS complicated with cardiomyopathies obtained from discharge sheets from Peking Union Medical College Hospital from January 1986 to August 2021 were collected. Case reports of CS complicated with cardiomyopathies were retrieved from PubMed. In addition, Cushing's disease (CD) patients without cardiomyopathies were collected as controls to compare the clinical features. Results: A total of 19 cases of CS complicated with cardiomyopathies and cases of CD without cardiomyopathies (n = 242) were collected. The causes of CS included pituitary adenoma (n = 8, 42.11%), adrenal adenoma (n = 7, 36.84%), ectopic adrenocorticotropic hormone (ACTH) tumor (n = 2, 10.53%) and unclear causes (n = 2, 10.53%) in the CS complicated with cardiomyopathies group. The types of cardiomyopathies were dilated cardiomyopathies (n = 15, 78.94%) and hypertrophic cardiomyopathies (n = 4, 21.05%). The serum sodium concentration was significantly higher [145.50 (140.50–148.00) mmol/L vs. 141.00 (140.00–143.00) mmol/L], while the serum potassium concentration was significantly lower [2.70 (2.40–3.60) mmol/L] vs. 3.90 (3.50–4.20 mmol/L)] in the CS complicated with cardiomyopathies group compared to the CD patients without cardiomyopathies. There were no significant differences between the CS complicated with cardiomyopathies group and the CD patients without cardiomyopathies in the serum cortisol concentration and 24-h urine free cortisol, but a significant difference in the adrenocorticotropic hormone level [109.00 (91.78–170.30) pg/ml vs. 68.60 (47.85–110.00) pg/ml]. Twelve/16 (75.0%) patients showed significant improvement or even a complete healing of the heart structure and function after remission of hypercortisolemia after treatment with CS. Conclusions: CS complicated with cardiomyopathies is a very rare clinical entity, in which cortisol plays an important role and it can be greatly improved after remission of hypercortisolemia.